Regime-dependent relationships among stock markets in Frankfurt, Vienna and Warsaw - Gurgul, Henryk (Managing global transitions, 2015)
This paper analyzes short-run relationships between German, Austrian and Polish stock market indices using the Markov Switching VAR (MSVAR) model. The impulse response function is used as the main tool and reveals two market phases. The results are useful for investors; reactions to disturbances are complex and depend on the market phase and the considered pair of variables. There is also a theoretical analysis of the msvar model. The theoretical unconditional characteristics of the process driven by the MSVAR model are presented along with calculation techniques which can be applied to other models.
Keywords: MSVAR; regime-dependent impulse response; dynamic relationship; z režimom pogojeni impulzni odzivi; Germany; Nemčija; Austria; Avstrija; Poland; Poljska; delniški trgi; dinamične zveze; Markov switching VAR; stock markets